The Comparative Effect of Different Timings of Whole Body Cryotherapy Treatment With Cold Water Immersion for Post-Exercise Recovery - Haq, Adnan; Ribbans, William J.; Hohenauer, Erich; Baross, Anthony W. (Frontiers in Sports and Active Living, 2022)
Despite several established benefits of Whole Body Cryotherapy (WBC) for post-exercise recovery, there is a scarcity of research which has identified the optimum WBC protocol for this purpose. This study investigated the influence of WBC treatment timing on physiological and functional responses following a downhill running bout. An additional purpose was to compare such responses with those following cold water immersion (CWI), since there is no clear consensus as to which cold modality is more effective for supporting athletic recovery. Thirty-three male participants (mean ± SD age 37.0 ± 13.3 years, height 1.76 ± 0.07 m, body mass 79.5 ± 13.7 kg) completed a 30 min downhill run (15% gradient) at 60% VO2 max and were then allocated into one of four recovery groups: WBC1 (n = 9) and WBC4 (n = 8) underwent cryotherapy (3 min, −120°C) 1 and 4 h post-run, respectively; CWI (n = 8) participants were immersed in cold water (10 min, 15°C) up to the waist 1 h post-run and control (CON, n = 8) participants passively recovered in a controlled environment (20°C). Maximal isometric leg muscle torque was assessed pre and 24 h post-run. Blood creatine kinase (CK), muscle soreness, femoral artery blood flow, plasma IL-6 and sleep were also assessed pre and post-treatment. There were significant decreases in muscle torque for WBC4 (10.9%, p = 0.04) and CON (11.3% p = 0.00) and no significant decreases for WBC1 (5.6%, p = 0.06) and CWI (5.1%, p = 0.15). There were no significant differences between groups in muscle soreness, CK, IL-6 or sleep. Femoral artery blood flow significantly decreased in CWI (p = 0.02), but did not differ in other groups. WBC treatments within an hour may be preferable for muscle strength recovery compared to delayed treatments; however WBC appears to be no more effective than CWI. Neither cold intervention had an impact on inflammation or sleep.